OTULIN deficiency in ORAS causes cell type‐specific LUBAC degradation, dysregulated TNF signalling and cell death. Issue 3 (25th February 2019) - Damgaard, Rune Busk; Elliott, Paul R; Swatek, Kirby N; Maher, Eamonn R; Stepensky, Polina; Elpeleg, Orly; Komander, David; Berkun, Yackov
Abstract: The deubiquitinase OTULIN removes methionine‐1 (M1)‐linked polyubiquitin signals conjugated by the linear ubiquitin chain assembly complex (LUBAC) and is critical for preventing TNF‐driven inflammation in OTULIN‐related autoinflammatory syndrome (ORAS). Five ORAS patients have been reported, but how dysregulated M1‐linked polyubiquitin signalling causes their symptoms is unclear. Here, we report a new case of ORAS in which an OTULIN‐Gly281Arg mutation leads to reduced activity and stability in vitro and in cells. In contrast to OTULIN‐deficient monocytes, in which TNF signalling and NF‐κB activation are increased, loss of OTULIN in patient‐derived fibroblasts leads to a reduction in LUBAC levels and an impaired response to TNF. Interestingly, both patient‐derived fibroblasts and OTULIN‐deficient monocytes are sensitised to certain types of TNF‐induced death, and apoptotic cells are evident in ORAS patient skin lesions. Remarkably, haematopoietic stem cell transplantation leads to complete resolution of inflammatory symptoms, including fevers, panniculitis and diarrhoea. Therefore, haematopoietic cells are necessary for clinical manifestation of ORAS. Together, our data suggest that ORAS pathogenesis involves hyper‐inflammatory immune cells and TNF‐induced death of both leukocytes and non‐haematopoietic cells. Synopsis: Mutations in the deubiquitinase OTULIN cause OTULIN‐Related Autoinflammatory Syndrome (ORAS), a TNF‐driven autoinflammatory disease in humans. While the cellular defects underlying the inflammation process remain unclear, a new case of ORAS sheds light on the pathogenesis and potential treatment. A homozygous Gly281 to Arg mutation in OTULIN leads to reduced activity and stability by unfolding the substrate‐binding site thereby causing ORAS in a consanguineous family. Patient‐derived dermal fibroblasts have impaired TNF signalling due to a concomitant reduction in expression of the linear ubiquitin chain assembly complex (LUBAC). OTULIN‐deficient human monocytes retains LUBAC expression and exhibits a hyper‐inflammatory phenotype with increased NF‐κB activation and spontaneous TNF secretion. Both patient‐derived fibroblasts and OTULIN‐deficient monocytes are sensitised to TNF‐induced cell death in the presence of additional stress, i.e. the protein synthesis inhibitor cycloheximide. Haematopoietic stem cell transplantation leads to complete remission in the patient showing that haematopoietic cells are necessary for ORAS manifestation and suggesting the pathogenesis involves TNF‐mediated inflammation and cell death. Abstract : Mutations in the deubiquitinase OTULIN cause OTULIN‐Related Autoinflammatory Syndrome (ORAS), a TNF‐driven autoinflammatory disease in humans. While the cellular defects underlying the inflammation process remain unclear, a new case of ORAS sheds light on the pathogenesis and potential treatment.